A low cost collision avoidance system based on a ToF camera for SLAM approaches - Romero-Godoy, Dayron (2022)
Indoor positioning is a problem that has not yet been solved efficiently and accurately. In outdoors the most effective solution is the Global Position System (GPS), but it cannot be used indoors due to the weakening of the signal, so other solutions have been studied. These approaches could be applied to define a map for the guidance of blind people, tourism or navigation for autonomous robots. In this paper, the study, design, implementation and evaluation of a robust obstacle detection and mapping system is proposed. Thus, it can be used to alert of near objects presence and avoid possible collisions in an indoor navigation. The system is based on a Time-of-Flight (ToF) camera and a Single Board Computer (SBC) like Raspberry PI or NVIDIA Jetson Nano. In order to evaluate the system several real experiments were carried out. This kind of system can be integrated on a wheelchair and help the handicapped person to move indoors or take data from an indoor environment and recreate it in a 2D or 3D images.